2015
DOI: 10.4238/2015.june.18.6
|View full text |Cite
|
Sign up to set email alerts
|

Association between IL-1β, IL-8, and IL-10 polymorphisms and risk of acute pancreatitis

Abstract: ABSTRACT.We assessed the possible correlation between genetic polymorphisms in interleukin (IL)-1β,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…Correlations between the IL-10 gene polymorphism and the development of acute pancreatitis have been investigated in several studies, and the results were inconclusive (Sargen et al, 2000;Schneider et al, 2004a,b;Zhang et al, 2005;de-Madaria et al, 2008;Bao et al, 2015;Li et al, 2015). Zhang et al (2005) conducted a study in a Chinese population, and they reported that the IL-10 -1082A/G gene polymorphism plays an important role in the susceptibility of acute severe pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlations between the IL-10 gene polymorphism and the development of acute pancreatitis have been investigated in several studies, and the results were inconclusive (Sargen et al, 2000;Schneider et al, 2004a,b;Zhang et al, 2005;de-Madaria et al, 2008;Bao et al, 2015;Li et al, 2015). Zhang et al (2005) conducted a study in a Chinese population, and they reported that the IL-10 -1082A/G gene polymorphism plays an important role in the susceptibility of acute severe pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that many lifestyle choices and environmental factors such as excessive drinking, pancreatic duct strictures, viral or bacterial infection, hyperlipidemia, metabolic disorders, and infections are associated with disease susceptibility (Álvarez et al, 2015;Greer et al, 2015;Pohl and Uc, 2015;Talukdar and Vege, 2015;Tun-Abraham et al, 2015). Recent studies have reported that genetic factors play an important role in the pathogenesis of acute pancreatitis, such as interleukin-1β (IL-1β), IL-8, IL-10, heme oxygenase-1 gene, Toll-like receptor gene, tumor necrosis factor alpha gene, and heat-shock protein 70-2 gene (Özhan et al, 2010;Bishehsari et al, 2012;Srivastava et al, 2012;Gulla et al, 2014;Li et al, 2015;Matas-Cobos et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Then 10 of the remaining 17 citations were removed after full text review. Finally 7 studies were included, [ 9 15 ] which targeted at either Asians [ 9 13 , 15 ] or Caucasians. [ 14 ] The characteristics of the included studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…IL-10 polymorphisms may induce genetic and molecular aberrations, which could result in the development of several types of autoimmune diseases including systemic lupus erythematosus, rheumatoid arthritis, ulcerative colitis, and Crohn's disease, in addition to acute pancreatitis (Amre et al, 2009;Marrakchi et al, 2009;Paradowska-Gorycka et al, 2010;da Silva et al, 2014;Lagha et al, 2015;Li et al, 2015;Talaat et al, 2015). Talaat et al (2015) reported an association between the clinical features and risk of systemic lupus erythematosus and IL-10 -1082G/A polymorphisms in an Egyptian population.…”
Section: Discussionmentioning
confidence: 99%